Stress and Happiness in Life of Students at Rajabhat University in Thailand - Tipvarin Benjanirat; Jatuporn Ounprasertsuk; Pongsak Jaroenngarmsamer; Phannee Rojanabenjakun; Sasipen Krutchangthong; Panupan Sripan; Sunatcha Chaowai (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Stress is related to happiness in student life, it is a condition in the body and stimulated torespond from inside and outside the body. The body or mind is out of balance, with each person showingdifferent stress affects the happiness in life in each period of that person.Objective: To examine the relationship between stress and the happiness of Rajabhat University studentsin Thailand.Material & Methods: This research was contextual research by using a cross-sectional survey. The sampleswere students selected the sample group by stratified proportion random simple and not overridden using arandom number table. The sample consisted of 190 students. The research instruments were self-reportedquestionnaires. The statistics used for data analysis were descriptive using inferential statistics to analyzerelationships with static chi-square.Results: The results of the research, most students have a high level of stress and rare happiness in life. Thestudy of the relationship between demographic factors, stress, and happiness in students’ lives found thatlevel education and family income have a relationship to the stress and gender associated with happiness.Stress was associated with happiness at a statistically significant level of 0.05.Conclusion: In this research, there are suggestions to study the cause of stress and ways to stress managementand the factors that contribute to the happiness of students to enable students to continue living in qualityteaching and learning